UNGKAPAN ETNIS PETANI JAWA DI DESA JAPANAN, KECAMATAN CAWAS, KABUPATEN KLATEN: KAJIAN ETNOLINGUISTIK - Haryanti Dwi; Agus Budi Wahyudi (Kajian Linguistik dan Sastra, 2007)
The study aims at describing ethnic expressions and their intention of Javanesefarmers at Japanan district based on their social and cultural context. It uses descriptivequalitative research and the data are analyzed by Spreadly’s ethnographicanalysis. The analysis tries to describe the linguistic units and their intension basedon the social and cultural contexts. The findings show that the ethnic expressionsconsist of words and phrases. Those expression are used in all steps of agriculturalactivities done by the farmers, for examples, pranatamangsa ‘months’, mangsa udan‘wet season’, macul ‘to hoe’, mangsa sada ‘the eleventh month’, gawe pinihan ‘cultivationof seedlings’, mangsa kanem ‘the sixth month’, ketiga ‘dry season’, luku andgaru ‘plows’, ngrabuk ‘to fertilize’, matun ‘to clear away the weeds in the farms’,mangsa panen ‘harvest moon’, dewi sri ‘rice’, den bagus ‘rats’, methik/guwakan ‘misticor ritual ceremony before harvesting time’, sedhekah bumi/bersih desa/rasulan ‘misticceremony after harvesting with wayang kulit show entitled sri boyong, sri mulih, or srisadana.